2013
DOI: 10.1021/ma401773w
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and Edge Effects on Swelling-Induced Ordered Structure Formation in Polyelectrolyte Hydrogels

Abstract: In this paper, we developed several kinds of ordered structures in hydrogels with different geometries and sizes by harnessing heterogeneous swelling induced mechanical instability, i.e., surface creasing, which leads to molecular orientations along the tensile direction. These hydrogels were synthesized by polymerization of a cationic monomer, N-[3-( N,N -dimethylamino)­propyl] acrylamide methyl chloride quaternary (DMAPAA-Q) and a chemical cross-linker, in the presence of a small amount of the semirigid poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 46 publications
(85 reference statements)
1
25
0
Order By: Relevance
“…The birefringence of the gel comes from both PBDT that has a positive birefringence and PDMAPAA-Q that has a negative birefringence. Previous study has shown that PBDT has a much stronger birefringence than PDMAPAA-Q, and the net birefringence observed here is related to the orientation of the rigid PBDT molecules [25][26][27] . From the birefringence colour observed with 530-nm-sensitive tint plate (Fig.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…The birefringence of the gel comes from both PBDT that has a positive birefringence and PDMAPAA-Q that has a negative birefringence. Previous study has shown that PBDT has a much stronger birefringence than PDMAPAA-Q, and the net birefringence observed here is related to the orientation of the rigid PBDT molecules [25][26][27] . From the birefringence colour observed with 530-nm-sensitive tint plate (Fig.…”
supporting
confidence: 57%
“…This internal-stressdirected orientation of rigid molecules inside the hydrogels has recently been demonstrated [24][25][26] . When both of the embedded rigid macromolecules and the hydrogels are polyelectrolytes but carry opposite charges, the orientation can be 'memorized' by polyion complex formation by the dialysis of their counterions 25,26 . Therefore, various superstructures of rigid polyelectrolytes could be developed in oppositely charged polymeric hydrogels by harnessing internal-stress-directed orientation of rigid macromolecules.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…[8][9][10][11][12][13] The latter perspective has enabled engineering opportunities with self-adaptive/autonomous structures in low dimensions and has implications in many different contexts such as micro-/ nanofluidics, [14][15][16] flexible electronics, [17,18] adhesion, [19,20] organic solar cells, [21] tunable optics, [22][23][24] wettability, [25][26][27] and promising methods for surface patterning. [1,[28][29][30][31] While our scientific/technical understanding has advanced, there remains much to be explored about the control of instability morphology, and in particular how to configure instabilities, such as wrinkling and creasing, to desired patterns with selective distribution covering the surface and bespoke thresholds for the formation and evolution of instabilities.…”
Section: Doi: 101002/adfm201704228mentioning
confidence: 99%
“…Such processes arise when an elastic material is compressed beyond a critical strain either by swelling, differential growth, or mechanical forces. In engineering, similar instabilities have long been thought of as nuisances, but they have recently found applications in many different contexts including flexible electronic devices [1][2][3][4], surface patterning methods [5][6][7][8] and materials with tunable optical properties [9][10][11][12], adhesion [13][14][15], and wettability [9,16,17].…”
Section: Introductionmentioning
confidence: 99%